2023
DOI: 10.1038/s41598-022-25400-1
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive liquid biopsy analysis as a tool for the early detection of minimal residual disease in breast cancer

Abstract: Liquid biopsy (LB) provides a unique minimally invasive tool to follow-up cancer patients over time, to detect minimal residual disease (MRD), to study metastasis-biology and mechanisms of therapy-resistance. Molecular characterization of CTCs offers additionally the potential to understand resistance to therapy and implement individualized targeted treatments which can be modified during the disease evolution and follow-up period of a patient. In this study, we present a long-term follow-up of operable breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 71 publications
1
12
0
Order By: Relevance
“…This association was stronger than the detection of ctDNA alone (hazard ratio =2.99), with similar trends observed for disease-free survival (DFS) and OS when comparing ctDNA+/CTCs+ to ctDNA−/CTCs−. Another recently published study offered insights into the role of comprehensive liquid biopsy analysis for the therapeutic management of EBC patients ( 33 ). Over a ten-year period, the study examined 13 EBC patients through multianalyte liquid biopsy approach, encompassing enumeration, phenotypic characterization, and molecular monitoring of CTCs along with corresponding ctDNA mutation and methylation profile.…”
Section: Ctcs and Ctdnasupporting
confidence: 56%
“…This association was stronger than the detection of ctDNA alone (hazard ratio =2.99), with similar trends observed for disease-free survival (DFS) and OS when comparing ctDNA+/CTCs+ to ctDNA−/CTCs−. Another recently published study offered insights into the role of comprehensive liquid biopsy analysis for the therapeutic management of EBC patients ( 33 ). Over a ten-year period, the study examined 13 EBC patients through multianalyte liquid biopsy approach, encompassing enumeration, phenotypic characterization, and molecular monitoring of CTCs along with corresponding ctDNA mutation and methylation profile.…”
Section: Ctcs and Ctdnasupporting
confidence: 56%
“…However, detecting tumor molecular abnormalities through liquid biopsy methods such as ctDNA and CTC indicates the persistence and clinical progression of the tumor ( 191 ). According to studies, liquid biopsies can detect metastatic diseases at least 4 years before they are clinically detected, indicating that thorough liquid biopsy evaluation of CTC combined with ctDNA monitoring MRD can provide very important information for treating and treating patients with breast cancer ( 192 ). Clinical studies have also shown the combination of CTC and ctDNA to improve the sensitivity and specificity of MRD detection in hepatic carcinoma ( 193 ).…”
Section: Comprehensive Liquid Biopsymentioning
confidence: 99%
“…Molecular characterization of CTCs based on gene expression, DNA methylation and DNA mutation analysis in combination with CTC count and phenotypic analysis can reveal the presence of MRD at least 4 years before the appearance of clinically detectable metastatic disease. This indicates that comprehensive liquid biopsy analysis could provide highly important information for the therapeutic management of breast cancer patients at early stages [ 17 ]. A recent study involving 1220 patients with stage I-III BrCa with more than ten-year follow-up has shown that the detection of CK-19 mRNA-positive CTC is prognostic for early relapse, supporting investigations for novel adjuvant therapeutic approaches [ 18 ].…”
Section: Ctc: Challenges For the Management Of Cancer Patientsmentioning
confidence: 99%